Wet strength improvement of pineapple leaf paper for evaporative cooling pad - T. Khampan (2018)
This research aimed to modify pineapple leaf paper (PALP) for using as wet media in the evaporation cooling system by improving wet mechanical property (tensile strength) without compromising water absorption property. Polyamideamineepichorohydrin resin (PAE) and carboxymethylcellulose (CMC) were used to strengthen the paper, and the PAE and CMC ratio of 80:20 showed the optimum wet and dry tensile index values, which were higher than those of the commercial cooling pad (CCP). Compared with CCP, PALP itself and all the PAE/CMC modified PALP possessed better water absorption. The PAE/CMC modified PALP had potential to become a new type of wet media.